2019
DOI: 10.1186/s41043-019-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between environmental factors and BMI: evidence from recent immigrants from developing countries

Abstract: Background To study the association between the surrounding local environmental factors and the body mass index of immigrants in the USA. Methods We use the New Immigrant Survey, to study the association of obesity prevalence in a region on body mass index. We consider local obesity rate as an outcome of the local environmental factors. Using ordinary least squares, three versions of equations are estimated to quantify the contribution of individual-level, acculturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Among the Wrocław residents of working age, women were found to be of normal body weight significantly more often than men. The results of earlier studies also confirmed this observation [2,23,24,35,36]. Interestingly, men are usually characterized by higher physical activity levels than women [15,37].…”
Section: Discussionsupporting
confidence: 66%
“…Among the Wrocław residents of working age, women were found to be of normal body weight significantly more often than men. The results of earlier studies also confirmed this observation [2,23,24,35,36]. Interestingly, men are usually characterized by higher physical activity levels than women [15,37].…”
Section: Discussionsupporting
confidence: 66%
“…All these bioactive compounds are reported as anti-bacterial effect. Inhibition zones ranged from 1.65 cm to 1.95 cm and maximum activity is found in aqueous extract of tamarind leaves as compared to the ethanol which is 1.9 (Katare and Hakrovorty, 2019).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 96%